THE INFLUENCE OF EVENING TWILIGHT ON THE ATTENTION OF DRIVERS OF DIFFERENT AGES IN CITY CONDITIONS - Prasolenko, O.; Afonin, M. (Municipal economy of cities. Series: «Economy science», 2024)
The article examines the issue of driver safety in cities in the evening twilight. A group of drivers aged 20 to 40 years with a total driving experience of 3 to 16 years was studied. Drivers with 3-5 years of driving experience had an average age of 25 years, and drivers with 10-16 years of driving experience had an average age of 34 years. Drivers drove along known routes at dusk and after dark. We measured drivers’ attention with a Pupil Labs headset, as well as functional state shifts with a respiratory rate monitor. The "Neulog Respiration Monitor Belt" device was used to determine the parameters of external breathing of drivers. Previously, we measured breathing parameters when the driver was in a calm state. Since the morning, the drivers’ breathing rate has been 10-12 breathing cycles. The results of the research indicate a significant difference in the shifts in the functional state during the movement along the routes for both groups. When the lighting changes from the beginning of the evening twilight, the energy consumption by drivers increases by 40%. At the same time, the maximum rate of energy consumption for the driver is 12.6 kJ/min, i.e. 2.9 kcal/min. Also, drivers with less driving experience were less attentive and more emotionally stressed. At the same time, the drivers of both groups experienced significant difficulties in reducing the lighting in the event of conflicting situations while driving. At the same time, energy expenditure significantly exceeded the limit indicators, and attention indicators worsened. This fact was observed after 15-20 minutes of driving in the evening twilight. The experimentally obtained data on changes in the driver’s attention index in the conditions of evening twilight can be used to build multifactorial models taking into account traffic parameters on different categories of streets. In the conditions of the evening twilight, the driver’s attention is significantly reduced. When the illumination changes from 50 lux (driving time 15-20 min.) and less, the driver experiences visual fatigue from constantly searching for objects on the road. At the same time, the number of fixations is significantly reduced, as the driver spends more time recognizing and searching for the necessary elements of the road environment, pedestrians, etc. Danger in the driver causes a state of stress, which is reflected in an increase in the driver’s breathing rate and, as a consequence, a change in the functional state. The main factor affecting the amount of energy spent in such conditions is the interaction of the driver with the road conditions. These factors require the driver to take certain actions when driving a car: acceleration, braking, maintaining speed and certain reactions in the event of a traffic hazard. The results of the analysis of parameters of the functional state of drivers with different years of work showed significant differences between electrophysiological indicators, both when moving in conditions of evening twilight and in background conditions. In the background conditions, lower values of electrophysiological indicators are primarily related to the different age of the drivers. Drivers with 3-5 years of driving experience had an average age of 25 years, and drivers with 10-16 years of driving experience had an average age of 34 years.